Pengaruh terapi relaksasi benson dan dzikir dalam menurunkan kecemasan pada pasien pra operasi sectio caesarea - Nur Afni Anggraini; Sujiah Sujiah; Dewi Yuliana (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Sectio caesarean section is a delivery procedure to remove the baby through an incision in the abdomen. The incidence of sectio caesarean section at Adventist Hospital has increased over the past 3 years, in 2022 as many as 315 patients, in 2023 as many as 377 patients, and in 2024 as many as 483 patients . Anxiety in preoperative patients, especially those who will undergo sectio caesarean section, can affect physical and mental health and can cause surgery to be delayed. Benson relaxation therapy and dhikr are expected to help lower anxiety levels in patients. Purpose: To determine the effect of Benson relaxation therapy and dhikr in reducing anxiety in preoperative patients with cesarean section Methods: This study uses a quasi-experimental design with a one-group pretest-posttest approach. The population in this study is all patients who will undergo sectio caesarean section at Bandar Lampung Adventist Hospital. Purposive sampling, consisting of 36 respondents who met the inclusion criteria. Data analysis used paired T-tests to compare anxiety levels before and after the intervention. Results: Data analysis using bivariate obtained the majority of respondents aged 26 to 28 years 14 people (38.9%), with the highest level of education being high school 21 people (58.3%), and the majority parity history in the second pregnancy 28 people (77.8%). In addition, the results of the paired T-test obtained a p value of 0.000 (p value ≤ 0.05), meaning that there is an Effect of Benson Relaxation Therapy and Dhikr in Reducing Anxiety in Pre-Caesarean Sectio Surgery Patients at the Adventist Hospital Bandar Lampung in 2025. Conclusion: There was a significant decrease in the level of patient anxiety, with a p value <0.05, which means that Benson relaxation therapy and dhikr were effective in reducing anxiety in pre-operative caesarean section patients.